Patellofemoral knee arthroplasty - Berruto, Massimo; Tradati, Daniele; Ferrua, Paolo; Maione, Alessio; Usellini, Eva (Annals of Joint, 2017)
Patellofemoral osteoarthritis (OA) is a common degenerative disease present in 10%-25% of patients presenting symptomatic knee OA. It can be found isolated or secondary to inflammatory joint diseases, patellar fractures and patellar instability. Anatomical abnormalities such as patella alta, altered patellar tilt and trochlear dysplasia can be identified as predisposing factors in patellofemoral OA etiopathology. In symptomatic patients with advanced stages isolated patellofemoral OA unicompartmental patellofemoral arthroplasty (PFA) is nowadays considered as the gold standard treatment. First reported by McKeever in 1955, PFA underwent a constant evolution in term of design and surgical techniques. Two kinds of prosthetic design are now available: resurfacing (so called inlay), in which the native trochlear shape and orientation remain unchanged with high bone preservation, and trochlear cutting (so called onlay) characterized by a wider asymmetrical trochlea with a higher level of patellar constraint. The success of replacement depends mainly on good patient selection and respect of relative and absolute contraindications. The outcomes are heterogeneous: recent studies about inlay generation showed a high revision rate (28%) at 6 years of follow-up. Onlay implants demonstrated a greater percentage of good to excellent results and survivorship, albeit inferior if compared to total knee arthroplasty. Early failure may be correlated to unexplained pain, progression of osteoarthritic process to femorotibial compartments and patellar maltracking, and late failure main cause remains progression of OA, followed by aseptic loosening and residual pain. In conclusion there is still no consensus for PFA indications and further long term and randomized studies are needed to assess the clinical benefits and long-term survivorship of this kind of implant.